Tactile-Feedback Stabilized Molecular Junctions for the Measurement of Molecular Conductance - Chen, I-Wen Peter; Tseng, Wei-Hsiang; Gu, Mong-Wen; Su, Li-Chen; Hsu, Chan-Hsian; Chang, Wei-Hsuan; Chen, Chun-hsien (Angewandte Chemie International Edition, 2013)
Handling the (AFM) tip: The duration of stable molecular junctions was prolonged using a tactile feedback method in which the operator can sense the force of the AFM tip on the sample surface (see picture). The movement of the tip is adjusted accordingly, maintaining a more consistent current (i) and voltage (V), instead of having the tip move at a constant preset speed, as in the conventional setup.